Foundations for the Design of a Creative System Based on the Analysis of the Main Techniques that Stimulate Human Creativity - De Garrido, L.; Gómez Sanz, J.J.; Pavón Mestras, Juan (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
This work presents the design of a computational system with creative capacity, based on the synthesis of the main methods that stimulate human creativity. When analyzing each method, a set of characteristics that the computer system must have in order to emulate a creative capacity has been suggested. In this way, by integrating all the suggestions in a structured way, it is possible to design the general architecture and functioning strategy of a computer system that has the incremental creative capacity of well-known creative methods. This computational system is designed as a multi-agent system, made up of two groups of agents, the problem solving group and the creative group, the first one exploring and evaluating paths for suitable solutions, the second implementing creative methods to generate new paths that are provided to the first group.
Keywords: artificial intelligence; creativity; creative system; multi-agent systems; lateral thinking; IJIMAI